Multiple cis regulatory elements for maximal expression of the cauliflower mosaic virus 35S promoter in transgenic plants. - Fang, R X (1989)
The 35S promoter is a major promoter of the cauliflower mosaic virus that infects crucifers. This promoter is still active when excised from cauliflower mosaic virus and integrated into the nuclear genome of transgenic tobacco. Previous work has shown that the -343 to -46 upstream fragment is responsible for the majority of the 35S promoter strength (Odell, J.T., Nagy, F., and Chua, N.-H. [1985]. Nature 313, 810-812). Here we show by 5', 3', and internal deletions that this upstream fragment can be subdivided into three functional regions, -343 to -208, -208 to -90, and -90 to -46. The first two regions can potentiate transcriptional activity when tested with the appropriate 35S promoter sequence. In contrast, the -90 to -46 region by itself has little activity but it plays an accessory role by increasing transcriptional activity of the two distal regions. Finally, we show that monomers and multimers of a 35S fragment (-209 to -46) can act as enhancers to potentiate transcription from a heterologous promoter.